2015
DOI: 10.3103/s1067821215020182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration during GTAW welding on microstructure and mechanical properties of Ti6Al4V

Abstract: Grain growth in Ti6Al4V alloy during fusion welding decreases yield stress and tensile strength. This study examined the effect of mechanical vibration of the work piece during GTAW welding on the mechanical and metallurgical properties of Ti6Al4V. The structures of all welded specimens at different levels of vibration was examined and it was found that, during 330 Hz vibration, grain size in the welded metal zone decreased significantly over that of pieces welded without vibration. GTAW at 330 Hz significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The issue of improving the micro and macro structural properties can generally be interpreted as improving metallurgical weldability, which has often been a priority [10]. A careful observer of the literature on the subject will notice that the majority of research in which the authors used mechanical vibrations focuses on the effects obtained, which undoubtedly leads in many cases to the fragmentation of grains [11], changing their shape into more equiaxial forms [12,13], improving mechanical properties such as strength, impact strength or hardness [14][15][16]. Few of these studies attached significant importance to technical problems associated with the effective introduction of vibrations and their form [2,17], and even more so with other parameters such as frequency, amplitude or phase [1,2,12,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of improving the micro and macro structural properties can generally be interpreted as improving metallurgical weldability, which has often been a priority [10]. A careful observer of the literature on the subject will notice that the majority of research in which the authors used mechanical vibrations focuses on the effects obtained, which undoubtedly leads in many cases to the fragmentation of grains [11], changing their shape into more equiaxial forms [12,13], improving mechanical properties such as strength, impact strength or hardness [14][15][16]. Few of these studies attached significant importance to technical problems associated with the effective introduction of vibrations and their form [2,17], and even more so with other parameters such as frequency, amplitude or phase [1,2,12,18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, full control of mechanical vibrations is only possible when they are introduced by a well-tested and rigidly mounted vibrating system [2,9,[13][14][15][18][19][20] or modulation of the electric arc [21][22][23] or laser beam [3]. The improvement of structural features and mechanical properties is obtained in various zones of welds or coatings, i.e., in the weld itself and in the heat-affected zone.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Compared with vibration-free welding, the grain of the vibration weld zone was refined from coarse columnar crystal to equiaxed crystal; the grain size was reduced by 36% and the yield strength, tensile strength, and hardness of the Ti 6 Al 4 V were improved. [15] Dendritic fracture was caused by mechanical vibration during solidification of an A356 aluminum alloy molten pool, refining grains and increasing equiaxed crystals. [16] Vibration-assisted welding not only had the advantages of changing the grain size of the melting zone and increasing the mechanical properties but also had a large effect on the size and grain size of the phase.…”
Section: Introductionmentioning
confidence: 99%
“…Castro et al successfully added the variable mechanism vibration in gas metal arc welding (GMAW), which proposed a new method to improve the mechanical and metallurgical properties. As vibration aging technology has been used in the field of welding, many researchers have focused on the effects of vibration on microstructure, grain size, crack sensitivity, and mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…As vibration aging technology has been used in the field of welding, many researchers have focused on the effects of vibration on microstructure, [16,17] grain size, [18] crack sensitivity, [19] and mechanical properties. [20,21] Mostafapour and Gholizadeh [22] examined the effect of mechanical vibration on mechanical properties and optimized the welding process to determine the optimum values of amplitude, frequency, and welding speed. Singh et al [23] explored the effect of vibration on the structural shape in the weld pool, and the experimental results showed that the vibration had significantly improved the mechanical properties of the welded joint.…”
Section: Introductionmentioning
confidence: 99%